-18-3x=6-4x

Simple and best practice solution for -18-3x=6-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -18-3x=6-4x equation:


Simplifying
-18 + -3x = 6 + -4x

Solving
-18 + -3x = 6 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-18 + -3x + 4x = 6 + -4x + 4x

Combine like terms: -3x + 4x = 1x
-18 + 1x = 6 + -4x + 4x

Combine like terms: -4x + 4x = 0
-18 + 1x = 6 + 0
-18 + 1x = 6

Add '18' to each side of the equation.
-18 + 18 + 1x = 6 + 18

Combine like terms: -18 + 18 = 0
0 + 1x = 6 + 18
1x = 6 + 18

Combine like terms: 6 + 18 = 24
1x = 24

Divide each side by '1'.
x = 24

Simplifying
x = 24

See similar equations:

| (-2+2v+2u)(-7)= | | -2*x+9=25 | | -2(r-6)=-37 | | 2*x+7=5 | | (y-15)-(1y-10)=19 | | 3(2x-5)-4(x-1)=(-3x-6)-3(x+3) | | 5*x+3=13 | | -9x-24=-11x+10 | | -6t=-39 | | log(x+15)-log(x)=0.65 | | 40x=18000+5y | | -47-91=156-9x | | -32-4x=46-x | | 2x-5=5-2 | | 5x-3(2x-10)=25 | | 34+03*2-25+5= | | z^2-(3+4i)z-1-5i=0 | | -46-(-28)= | | 78+n=3n-40 | | 5y-8=12x+4 | | 5y+24=y-8 | | 1.84g-8=0.28 | | 48=3.2x | | 4x+8-8x=32-4x | | 84+n=36-3n | | 3y-18=6 | | 7-1.5x=62.5 | | 4x-47=7x+22 | | 5+5+5+5+5=555 | | 7-1.5x=64 | | 4x-2x=7+13 | | 4a+3=3a+13 |

Equations solver categories